Differential and tissue-specific regulation of the multiple rat c-erbA messenger RNA species by thyroid hormone. - Hodin, R A (1990)
Thyroid hormone (T3) has been shown to regulate the level of its receptor in a number of tissues and cell lines. Recently, proteins encoded by the protooncogene c-erbA have been identified as T3 receptors. In the rat, four c-erbA gene products have been isolated, three of which, r-erbA alpha-1, r-erbA beta-1, and r-erbA beta-2, encode biologically active T3 receptors; the fourth, r-erbA alpha-2, may play an inhibitory role in T3 action. The present work examines the molecular nature of T3 receptor autoregulation using probes specific for each c-erbA mRNA. Rats were rendered hypothyroid with propylthiouracil and then treated with either saline or T3. Northern blot analyses reveal marked tissue-specific and differential regulation of the multiple c-erbA mRNAs by T3. In the pituitary the levels of r-erbA beta-1 mRNA increase, whereas the levels of the pituitary-specific r-erbA beta-2 mRNA decrease with T3 treatment. In heart, kidney, liver, and brain the levels of r-erbA beta-1 are unaffected by thyroidal status. The levels of both r-erbA alpha mRNAs decrease with T3 treatment in all tissues examined except for the brain, where there is no change. In addition, we find that changes in the mRNAs encoding specific subpopulations of T3 receptors do not always parallel changes in total nuclear T3 binding. Differential regulation of the specific c-erbA mRNA species could have important consequences for T3 action.